Farmers’ Appraisal on Okra [Abelmoschus esculentus (L.)] Production and Phenotypic Characterization: A Synergistic Approach for Improvement - Ibitoye, Dorcas Olubunmi; Kolawole, Adesike Oladoyin (Frontiers in Plant Science, 2022)
Okra [Abelmoschus esculentus (L.) Moench] is a nutrient-rich economically important vegetable crop grown in tropical and sub-tropical regions of the world. Okra is one of the horticultural mandate crops of the National Horticultural Research (NIHORT), Ibadan, Nigeria. It is an under-studied crop in terms of genetic improvement in Nigeria. In response to farmers’ demand for improved varieties, the institute commenced efforts in developing novel okra varieties. However, a successful and sustainable crop improvement program depends on the identification of market-driven demands and the availability of variation in the crop germplasm. In view of the above, this research began with an appraisal study to assess the current situation of okra production and to identify farmers’ preferred traits for establishing breeding priorities. According to the results of the participatory rural appraisal, some of the important constraints affecting okra productivity are lack of improved varieties, diseases, pests, and drought. The quest to assess variability in the collected okra accessions and select superior varieties with farmers’ preferred traits, fifty (50) okra accessions were evaluated in the field for 3 consecutive years (2019–2021) using a 5 × 10 α-lattice incomplete block design with three replications. The ANOVA revealed high significant variation (p < 0.001) in the number of days to first flower, pod length, and pod girth. The variability observed among the accessions will be useful in the selection of potential parents required for hybridization and generation of progenies with desirable traits for farmers.